2023
DOI: 10.3390/polym15071802
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Properties of Raw and Alkali Treated Novel Cellulosic Root Fibres of Zea Mays for Polymeric Composites

Abstract: Today, new materials based on natural fibres have been emerging day by day to completely eradicate plastics to favour our environmental nature. In this view, the present work is based on the extraction and characterisation of the novel root fibres of the Zea mays (Zm) plant, grown by the hydroponic method. Both the dried untreated and alkali treated root fibres are investigated using a variety of structural, morphological, thermal, elemental and mechanical tests by subjecting both the samples to p-XRD, FT-IR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 71 publications
2
8
0
Order By: Relevance
“…It is widely acknowledged that lignocellulosic fibers with high crystallinity exhibit favorable characteristics such as high density, dimensional stability, and tensile strength while their chemical reactivity and swelling ability are reduced . A similar trend was reported previously by Kavitha et al, Xu et al, Al Abdallah et al, Sosiati et al, and Husnil et al where crystallite size and crystallinity were found to be increased after the alkaline treatment process.…”
Section: Resultssupporting
confidence: 83%
“…It is widely acknowledged that lignocellulosic fibers with high crystallinity exhibit favorable characteristics such as high density, dimensional stability, and tensile strength while their chemical reactivity and swelling ability are reduced . A similar trend was reported previously by Kavitha et al, Xu et al, Al Abdallah et al, Sosiati et al, and Husnil et al where crystallite size and crystallinity were found to be increased after the alkaline treatment process.…”
Section: Resultssupporting
confidence: 83%
“…A lengthy tradition of using maize husks in folk art has resulted in items such as corn husk dolls and woven amulets. In this study, corn was cultivated hydroponically, and the root fibres were employed for further investigation 30 32 .…”
Section: Methodsmentioning
confidence: 99%
“… where K is the sample's coefficient of thermal conductivity; m is the metal disc's mass; c is the heat capacity, and dT/dt is the rate at which the metal disc cools. (T 2 —T 1 ) is the temperature difference over the thickness of the sample, and x is its thickness; R is the sample’s radius, and h is the metal disc's thickness 30 .
Figure 3 Lee’s Disc Experimental set-up.
…”
Section: Methodsmentioning
confidence: 99%
“…Natural fibre-reinforced polymer composites have gained significant importance in a variety of automotive and civil applications [16,17]. Natural fibre composites are used in industries other than the automotive, such as in building and construction [18,19], sports, and aerospace. Panels, window frames, decking, and bicycle frames are some examples [20].…”
Section: Introductionmentioning
confidence: 99%